2018
DOI: 10.1097/wco.0000000000000519
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of vestibular syndromes

Abstract: Most of episodic or progressive syndromes show familial clustering. A detailed phenotyping with a complete familial history of vestibular symptoms is required to conduct a genetic study. Progress in these studies will allow us to understand diseases mechanisms and improve their current medical treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 60 publications
0
14
0
1
Order By: Relevance
“…Over the last 20 years, many candidate genes have been proposed for MD based on the so-called "common diseasecommon variants" paradigm that prevailed in complex disease genetic studies (8)(9)(10). It was thought that the common variants may lead to genetic susceptibility to complex polygenic disease (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last 20 years, many candidate genes have been proposed for MD based on the so-called "common diseasecommon variants" paradigm that prevailed in complex disease genetic studies (8)(9)(10). It was thought that the common variants may lead to genetic susceptibility to complex polygenic disease (43).…”
Section: Discussionmentioning
confidence: 99%
“…Most MD cases are sporadic, but familial MD is observed in 8-10% of sporadic cases, suggesting genetic susceptibility to the development of MD (3)(4)(5). To search a candidate gene associated with MD, many approaches including linkage analysis, case-control study or the sequencing of selected genes have been previously used (6)(7)(8)(9)(10). A variety of common single nucleotide polymorphisms (SNPs) have been meaningfully detected in patients with MD (Supplementary Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies indicate that MD is most common in European population, suggesting a genetic predisposition (Ohmen et al 2013). Although the majority of MD patients are considered sporadic (Frejo et al 2016; Frejo et al 2017), familial clustering has been reported in 8-9% of sporadic cases in the European descendent (Requena et al 2014), and in 6% of Korean population (Lee et al 2015), which also supports a genetic contribution to the disease (Roman-Naranjo et al 2017). MD shows a wide range of phenotypic variations among patients, even within the same families (Lee et al 2015b), and it is commonly associated with migraine and systemic autoimmune disorders (Tyrrell et al 2014; Cha et al 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Most cases of VM are considered sporadic, but familial aggregation of VM with autosomal-dominant inheritance has been described in several families, supporting a genetic background for the condition (3,4). Genome-wide association studies (GWASs) have identified numerous single-nucleotide polymorphisms (SNPs) associated with a genetic predisposition for migraine with or without aura (5,6).…”
Section: Introductionmentioning
confidence: 99%